An Analysis of Argumentative Essay Writing Errors of EFL Students in Palembang: A Study of Three Universities - Astrid, Annisa; Basri, Tiffanie; Dwi Amrina , Rizqy (Unib Press, 2025)
This research was conducted in three universities in Palembang: UIN Raden Fatah Palembang, Universitas Sriwijaya, and Universitas Muhammadiyah Palembang. The total sample of this research was 30 students. In this study, test and checklists error were used as the research's instruments for gathering data. This study adopted Langan’s classification of errors, which categorized errors into four types: unity, support, coherence, and sentence skills. The findings of this study revealed four writing errors in students' essays. 1) Students of three universities in Palembang as the sample of study contributed four types of errors in their essay writing, those were (1) unity (6,48%), support (14,21%), coherence (11,97%), and sentence skills (67,33%). 2) The most common errors in essay writing contributed by three universities students in Palembang was sentence skills with the occurrence 270 errors (67,33%). The urgency of this research lies in the critical role that effective writing skills play in academic success and professional communication. Despite the increasing demand for proficient writing abilities in higher education, many students still struggle with fundamental aspects of essay writing. Identifying and addressing these issues is essential for improving students’ academic performance and preparing them for future career challenges.